OPTIMALISASI STRATEGI PENGADAAN SARANA DAN PRASARANA DI MTSS MIFTAHUL HUDA: ANALISIS KENDALA PENDANAAN DAN DAMPAK TERHADAP KUALITAS PEMBELAJARAN - Fitria Salsabila; Ridha Ramadhani; Nur Azizah; Rasikha Auliya Arifin; Zahrotul Munawwaroh (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study examines the procurement strategy for educational facilities and infrastructure at MTs Miftahul Huda, emphasizing optimization amid funding constraints from BOS funds, student fees, and foundation aid. Employing a qualitative descriptive approach via literature review and observation, findings reveal that the madrasah prioritizes comprehensive evaluation of existing assets, repair-first policies based on cost-benefit analysis (under 40% of new replacement value), and community gotong royong to save up to 60% of the annual budget. Primary challenges include funding shortages delaying repairs for desks, chairs, and fans, which affect learning comfort; adaptive measures like needs prioritization and foundation coordination effectively mitigate these issues. Results indicate that this contextual strategy enhances managerial efficiency while supporting teaching-learning quality, though long-term planning is needed for broader applicability.